Posonskyi S.F., Babak О.P. Optimization of technological parameters of induction surfacing by composite powder of made from l53 steel working units of the soil-processing machines - Посонський, С.Ф.; Бабак, О.П. (Problems of Tribology, 2017)
The influence of soil composition on the wear of soil-processing machines’ working units is investi-gated. The working units of soil-processing machines are subjected to the greatest deterioration when working on heavy loamy and sandy-gravel soils that require high hardness of soil-processing machines’ working units’ surface. Numerous tests of serial details of domestic plow cases show that the average failure rate, depending on the types of soils and their physical state, varies from 5 to 20 hectares. A number of new technologies have been developed to increase the resource of working bodies. Appli-cable technology of restoration should provide the creation of a reliability reserve of recovery technological process. The induction surfacing with composite powders, the composition of which greatly affects the charac-teristics of soil-processing machines’ working units, possesses wide possibilities. The influence of technological parameters of the process of induction surfacing with composite powder for plaque made of steel Л53 with ob-taining the optimal restoration parameters on the maximum hardness of the deposited layer is investigated. By the method of mathematical planning of the experiment, the optimum parameters of induction sur-facing of the plow from the steel Л53 with composite powder were obtained, which were based on the criterion of maximum hardness of the surface layer (56 HRC). Managing the composition of the ПГС-27+ПФЛ surfacing composition allows providing various me-chanical and technological properties of the surfaced layer. Keywords: wear resistance, hardness, flux-doping powder, technological parameters of recovery, factor experi-ment, optimal parameters.